2023
DOI: 10.1021/acs.jafc.3c00776
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Mechanism of Prenylated Flavonoids Isolated from Mulberry Leaves on α-Glucosidase by Multi-Spectroscopy and Molecular Dynamics Simulation

Abstract: Flavonoids have always been considered as the chemical basis for the hypoglycemic effect of mulberry leaves. In the course of our search for hypoglycemic effect agents from natural sources, a systematic study was launched to explore prenylated flavonoids from mulberry leaves. Herein, chemical investigation led to the isolation of 10 characteristic prenylated flavonoids, including two new compounds (1 and 3). Their structures were elucidated based on spectroscopic data. All compounds exhibited good α-glucosidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Although the precise chemical responsible for this benefit is unknown, the ancient Chinese medicinal book Qi Min Yao Shu referenced the effect of mulberry leaf as traditional Chinese medicine to alleviate diabetes. Some previous studies reported that the mulberry leaf extracts showed excellent α-glucosidase inhibitory activity [18,20]. Pre-experiment results indicated that α-glucosidase inhibitory activity of mulberry leaf peptides from our cultivated high-protein variety was closely related to the molecular weight and peptide sequence.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Although the precise chemical responsible for this benefit is unknown, the ancient Chinese medicinal book Qi Min Yao Shu referenced the effect of mulberry leaf as traditional Chinese medicine to alleviate diabetes. Some previous studies reported that the mulberry leaf extracts showed excellent α-glucosidase inhibitory activity [18,20]. Pre-experiment results indicated that α-glucosidase inhibitory activity of mulberry leaf peptides from our cultivated high-protein variety was closely related to the molecular weight and peptide sequence.…”
Section: Introductionmentioning
confidence: 75%
“…The solvent accessible surface area (SASA) of different complexes reveals the enzyme folding stability (Figure 7d) [20]. The SASA values of all complexes tended to be stable and had similar changes within 10 nm 2 .…”
Section: Solvent Accessible Surface Area Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Natural resources, such as traditional herbs and functional fruits, are abundant with biologically interesting compounds, which have been widely explored for the development of naturally occurring inhibitors on α-glucosidase. For example, narcissoside isolated from Anoectochilus roxburghii [7], trilobatin obtained from Lithocarpus polystachyu [8], prenylated flavonoids isolated from mulberry leaves [9], and furanolabdane diterpenoids from the tropical plant Graptophyllum pictum [10] are reported to exhibit an excellent inhibitory effect on α-glucosidase, showing high application potential as natural antidiabetic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that hesperidin exhibits a considerable inhibitory effect against αglucosidase [18,19]; however, the inhibitory mechanism remains unknown, which greatly restricts its further application for the management of diabetes. With the rapid development of spectroscopic analysis and computer simulation techniques, multiple methods, such as the fluorescence spectrum, calorimetric analysis, and molecular modeling calculation, have been widely explored to elucidate the action mode between the small molecule and bio-macromolecule [8,9]. Therefore, in the present study, the inhibitory effect and the action mode of hesperidin binding to α-glucosidase were investigated through in vitro enzyme kinetics, a fluorescence quenching assay, and molecular docking studies for the first time.…”
Section: Introductionmentioning
confidence: 99%